Nursing management of nasogastric tube feeding and hypoglycemia prevention in an elderly patient with diabetes mellitus and cerebral infarction (1例老年糖尿病合并脑梗死患者鼻饲护理及低血糖预防) - ZHEN Chao (郑超); CAO Hongjing (曹红京) (Association of Integrative Nursing, 2021)
This paper reviewed the clinical data of an elderly patient with diabetes mellitus and cerebral infarction, and summarized individualized nursing measures. The patient received diabetic diet by nasogastric tube feeding, and patient's blood glucose level was carefully observed during insulin injection therapy. Individualized nursing measures included diet nursing, nasogastric tube management, hypoglycemia prevention and control, oral care, skin care. (本文回顾1例老年糖尿病合并脑梗死患者的临床资料, 总结个体化护理措施。患者入院后给予糖尿病鼻饲饮食, 胰岛素注射治疗期间密切监测血糖水平。个体化护理措施包括饮食护理、鼻饲护理、低血糖预防和处理、口腔护理、皮肤护理等。)